Semaglutide in Patients with Heart Failure with Preserved Ejection Fraction and Obesity - Kosiborod, Mikhail N.; Abildstrøm, Steen Z.; Borlaug, Barry A.; Butler, Javed; Rasmussen, Søren; Davies, Melanie; Hovingh, G. Kees; Kitzman, Dalane W.; Lindegaard, Marie L.; Møller, Daniél V.; Shah, Sanjiv J.; Treppendahl, Marianne B.; et al. (The New England journal of medicine, 2023)
In patients with heart failure with preserved ejection fraction and obesity, semaglutide (2.4 mg) led to greater reductions in symptoms and physical limitations and greater improvements in exercise function than placebo.